Navegar é preciso: a internet como ferramenta suplementar na leitura e escrita em inglês - Fonseca, Hejaine de Oliveira (2007)
This investigation was aimed at analyzing possibilities and contributions of the Internet as a supplementary tool to the English teaching and learning process, focusing on reading and writing skills, as well as on the learner s autonomy. We also aimed at analyzing e-Proinfo courseware´s contribution as a tool used to host and manage on-line courses offered as a complement to traditional classroom settings. We designed the online complementary activities following the principles of task-based language learning and teaching and those underlying the communicative approach and reading and writing theories. To collect and analyze the data the following research instruments were used: questionnaires, e-Proinfo interaction tools (forum and diary log), reading and writing activities on the e-Proinfo virtual environment, and interviews. The participants of this study were 8th term students of a Language Education Undergraduate Course whose participation in a reading and writing virtual course offered as a complement to the traditional classes was observed. The outcome reveals that the goals of this research paper were reached because the learners could do the proposed tasks, demonstrating some changes in their reading and writing processes and also in their computing skills. As to their reading skills, the learners mentioned to have enhanced their reading habits and their taste for books. They also revealed to have acquired new learning strategies, claiming that they have avoided using dictionaries, made more use of the context, titles and general information, thus, sped up the reading process. Furthermore, the learners revealed to better understand structures such as present perfect, present perfect continuous, time clauses, phrasal verbs, imperative and warning and advice expressions. As to their writing skills, students claim to have improved by making a better use, at the end of the course, of structures involving the present perfect, second conditional, verbs (would/would like) and opinion, wishes and greeting expressions. Moreover, the learners have become more critical and aware of their writing process. As to their autonomy, we could observe that the participants became more autonomous, trying to solve the problems they came across, helping their classmates and acquiring new behavior related to their learning practice. As to new technologies, the learners revealed to have improved computing skills, such as researching on the web, sending e-mails and virtual cards, etc. As to the e-Proinfo courseware, considering the researcher s perspective, we came to the conclusion that this technological resource is satisfactory, for it makes many resources available for the implementation of virtual courses, consequently, facilitating its use. As to the user s perspective, the information obtained indicated that this courseware presents itself as an interesting, organized and easy to use, since all the participants, even those who were not digitally literate, claimed to use it without difficulties. Further studies must be carried out to better understand the process of writing classroom activities in virtual environments, focusing on the aspects of text organization, as well as on other aspects related to the use of new technologies, such as technophobia, cognitive changes and interaction in a virtual environments.